Transition form factors: γ∗+p → Δ (1232), Δ (1600) - Lu, Y.; Chen, C. [UNESP]; Cui, Z. F.; Roberts, C. D.; Schmidt, S. M.; Segovia, J.; Zong, H. S. (American Physical Society (APS), 2019)
Electroproduction form factors describing the γ∗p→Δ+(1232), Δ+(1600) transitions are computed using a fully dynamical diquark-quark approximation to the Poincaré-covariant three-body bound-state problem in relativistic quantum field theory. In this approach, the Δ(1600) is an analogue of the Roper resonance in the nucleon sector, appearing as the simplest radial excitation of the Δ(1232). Precise measurements of the γ∗p→Δ+(1232) transition already exist on 0≤Q2≲8 GeV2, and the calculated results compare favorably with the data outside the meson-cloud domain. The predictions for the γ∗p→Δ+(1600) magnetic dipole and electric quadrupole transition form factors are consistent with the empirical values at the real photon point, and extend to Q2≈6mp2, enabling a meaningful direct comparison with experiment once analysis of existing data is completed. In both cases, the electric quadrupole form factor is particularly sensitive to deformation of the Δ-baryons. Interestingly, while the γ∗p→Δ+(1232) transition form factors are larger in magnitude than those for γ∗p→Δ+(1600) in some neighborhood of the real photon point, this ordering is reversed on Q2≳2mp2, suggesting that the γ∗p→Δ+(1600) transition is more localized in configuration space.